Lexico-semantic Analysis of V. Bryusov’s Image in M. Tsvetaeva’s Sketch “Labor Hero” - Alexandra A. Kozakova (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2018)
The center of M. Tsvetaeva’s attention is remarkable and complex personality of V. Bryusov, who evoked very contradictory feelings from admiration and immense respect to fierce hatred in many contemporaries. It is precisely the desire to reveal the whole breadth and ambiguity of the nature of V. Bryusov that leads Tsvetaeva not only to create an original composition, but also to a very peculiar selection of vocabulary to characterize his character. The peculiarity of this lies primarily in the fact that from the very first lines of the essay, most of Bryusov’s color definitions really have negative (and sometimes sharply negative) terms of connotation (anti-music, barbarian gesture, hostility, Salieri, and many others). The hostility and danger emanating from Bryusov (in the perception of Tsvetaeva) is also emphasized by his constant comparison with the wolf. Such a selection of words and analogies creates, at first glance, a portrait of a rather unpleasant person who considers himself a poet, but is devoid of creative (divine) principle. But with a deeper analysis in the stream of negative characteristics, words (and concepts) are revealed that have a special meaning for Tsvetaeva, with the help of which the poet builds his strong “monument to Bryusov”. The words of “positive” semantics are much less than the lexemes of the previous group. But they play a very important role in creating the image of the protagonist. The most important lexemes are wolf, will, Roman, labor. Thus, Tsvetaeva originally decided the difficult task of showing the greatness of V. Bryusov, while maintaining an ambiguous attitude towards him.